Water losses in the inner delta of the River Niger: water balance and flooded area - Mahe, G.; Bamba, F.; Soumaguel, A.; Orange, Didier; Olivry, J.C. (Wiley, 2009)
The inner delta of the River Niger receives runoff from both the River Niger and the River Bani (249 000 km2) and is divided into a northern part (15 000 km2) and a southern part (58 000 km2). The average input and output discharges are approximately 1490 and 900 m3 s1 (1955/1996), respectively. The annual average water loss is approximately 40% (24-48%). The losses are greater in the northern (10?5 km3) than in the southern delta (8?2 km3), but this situation was reversed in 1984. The correlation between the output and input discharges is high for the northern part of the delta, but very low for the southern part, where the change in flooded area is likely to be limited. The average flooded area, calculated using a method based on the hydrological balance, is estimated to be about 10 000 km2 (north) and 14 000 km2 (south), which is consistent with the estimates provided by the previous authors.